Metals immobilization and removal rates of Se(IV) and Se(VI) by steel slag fines media - Wazne, M. (2017)
Batch kinetics and column studies were conducted using freshly crushed steel slag fines (SSF) media to immobilize Se(IV) and Se(VI). The SSF media was characterized as USCS SP type soil with <5% passing the No. 200 (0.075 mm) sieve. Despite its granular nature, the mineralogy and residual lime content of the SSF media make it quite reactive. Accordingly, batch (immobilization) rates of Se by the SSF media were evaluated using aqueous Se(IV) and Se(VI) salt solutions having target doses equivalent to 10,000 mg/kg (500 mg/L equivalent). The percent removal of Se(VI) and Se(VI) by SSF was about 94% and 6%, respectively after 18 hrs mixing time. Column studies were also conducted to evaluate the selenium removal at lower influent concentrations (30 to 40 mg/L), but typically in excess of dissolved Se concentrations observed in the Western US groundwaters and acid mine drainage leachates.